Pengaruh Digital CRM melalui Aplikasi Alfagift terhadap Loyalitas Pelanggan Alfamart Wilayah Kecamatan Cikedung, dengan Kepuasan Pelanggan sebagai Variabel Mediasi - Ma’arif, Putuhal; Sugiarto, Sugiarto; Yudianto, Agus (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of Digital Customer Relationship Management (Digital CRM), implemented through the Alfagift application, on Alfamart customer loyalty, with customer satisfaction serving as a mediating variable. The research is motivated by the increasing competition in modern retail, which requires companies to integrate digital services into long-term customer relationship strategies. Using a quantitative approach, data were collected through questionnaires from 100 Alfagift users in the Cikedung area who were selected based on specific criteria. Multiple regression analysis and the Sobel test were used to examine the hypotheses. The results show that Digital CRM through Alfagift (X) has a positive and significant influence—both directly (partial pathway) and simultaneously—on customer loyalty (Y). This finding is supported by a t-value of 5.066 with a significance level of 0.000. The study also confirms that customer satisfaction (Z) is a strong determinant of loyalty, indicated by a t-value of 2.996 and a significance level of 0.003. Most importantly, the mediation test (Sobel Test: Z = 2.224; p-value = 0.0261) demonstrates that customer satisfaction partially mediates the relationship between Digital CRM and customer loyalty. Overall, this research concludes that Alfamart customer loyalty is driven not only by the effectiveness of Digital CRM but also by the ability of the Alfagift application to create valuable experiences that lead to increased customer satisfaction. Practical implications highlight the need to optimize feature personalization and improve application interface quality to strengthen sustainable customer relationships.